Reduced order multiscale model for compression kink-band failure in composites. (September 2022) - Faupel, Alex; Meshi, Ido; Oskay, Caglar
A multiscale model for compression kink band failure in fibrous composites is presented. The computational model predicts the progression of damage associated with the formation of kink bands, which experiments demonstrate to involve excessive shear straining of the matrix material and fiber fracture. The uniqueness of the study is establishing the concurrent treatment of nonlinear deformation and failure of the composite constituents at the scale of the material microstructure, and the formation of kink bands at the mesoscopic scale. The model incorporates computational homogenization of the material response, a nonlocal gradient regularization scheme, and a curvature-based criterion for macroscopic fiber break to predict kink band formation. The multiscale approach resolves mesoscale mechanisms associated with kink banding while offering computational benefits compared to direct mesomechanical approaches. An accessible implementation within finite element analysis software is presented and the model is verified with analysis of a mesoscale domain incorporating initial fiber waviness. In quasi-static simulations, the kink band initiates due to matrix softening that results in the onset of buckling and is completely formed when fibers break as a result of localized curvature. Results from parametric studies confirm that compression strength is not directly related to measures of the kink band morphology, but it is strongly correlated with the shear strength and initial fiber misalignment angle. The predicted effects of material properties representing various carbon fiber reinforced polymers and a range of fiber misalignment angles on kink band width and failure strength corroborate analytical and experimental results presented in the literature.